THE EFFECTIVENESS OF TEACHING ENGLISH IN HIGH SCHOOLS OF UZBEKISTAN - Mavlonova Rukhshona,; Ibadova Nafisa Axmatilloyevna, (Лучшие интеллектуальные исследования, 2023)
Annotation: Here's an extended version of the article on "The Effectiveness of Teaching English in High Schools of Uzbekistan."